2017
DOI: 10.1093/cid/cix693
|View full text |Cite
|
Sign up to set email alerts
|

Trial Evaluating Ambulatory Therapy of Travelers’ Diarrhea (TrEAT TD) Study: A Randomized Controlled Trial Comparing 3 Single-Dose Antibiotic Regimens With Loperamide

Abstract: NCT01618591.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 34 publications
1
30
1
Order By: Relevance
“…The study design and results of the clinical trial have been previously reported [ 11 ]. The study was approved by the Uniformed Services University Infectious Disease Institutional Review Board, United Kingdom Ministry of Defence Research Ethics Committee, and the Kenya Medical Research Institute Ethical Review Committee.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study design and results of the clinical trial have been previously reported [ 11 ]. The study was approved by the Uniformed Services University Infectious Disease Institutional Review Board, United Kingdom Ministry of Defence Research Ethics Committee, and the Kenya Medical Research Institute Ethical Review Committee.…”
Section: Methodsmentioning
confidence: 99%
“…The Trial Evaluating Ambulatory Therapy for TD (TrEAT TD) study evaluated the effectiveness of single dose antibiotic therapy for treatment of ambulatory TD in deployed UK and US military personnel [ 11 ]. Subjects provided a stool sample prior to therapy, a portion of which was smeared onto a FTA card and another frozen in a cryovial.…”
Section: Introductionmentioning
confidence: 99%
“…103 In this study, U.S. and U.K. adults with acute non-inflammatory diarrhea at four military deployment sites in Afghanistan, Djibouti, Kenya, and Honduras were randomized and received single-dose levofloxacin (500 mg; 111 persons), azithromycin (500 mg; 106 persons), and rifaximin (1650 mg, 107 persons) plus loperamide (labelled dosing). The primary outcome of clinical cure was evaluated in a non-inferiority trial design with azithromycin and rifaximin versus a levofloxacin standard.…”
Section: Methodsmentioning
confidence: 99%
“…In this investigation, we characterized a collection of EAEC strains isolated from DMP enrolled in the Trial Evaluating Ambulatory Therapy of Travelers' Diarrhea (TrEAT TD) Study (Riddle et al, 2017) by whole genome sequencing and analysis, biofilm formation, adherence to HEp-2 cells, and, for a subset, the capacity to cause failure-to-thrive (FTT) in an Amp-treated mouse model with the goal of identifying a genotype more associated with TD in the DMP population.…”
Section: Introductionmentioning
confidence: 99%